Enhanced Electron Tomography with Sequential Statistical Reconstruction by Missing-wedge Gap-information Filling - Paavolainen , Lassi; Soonsawad , Pan; Acar , Erman; Ruotsalainen , Ulla; Cheng , R. Holland (Current Topics on Chemistry and Biochemistry Vol. 6, 2022)
Electron tomography of biological samples is used to study the organization and the structure of the whole cell and subcellular complexes. We achieve isotropic resolution with a statistical reconstruction method, sequential maximum a posteriori expectation maximization (sMAP-EM), to resolve missing projections in transmission electron microscopy over incomplete tilts of tomography data. Evaluated by the symmetricity of gold particles, an ellipsoid fitting-based method was developed to realize the quantitative measures of elongation and contrast in an automated and objective way in producing isotropic resolution. Moreover, quantitative assessments were performed comparatively with reconstructions made with widely-used weighted back projection and simultaneous iterative reconstruction technique methods. We improved the contrast ratio, enhancing the applicability of further automatic and semi-automatic analysis. The method statistically evaluates the sub-volumes containing gold particles randomly located in various parts of the whole volume, thus indicating the robustness of the volume improvement. The improved 3D reconstruction by sMAP-EM enables an analysis of subcellular structures with enhanced three-dimensional resolution and contrast to conventional methods.